Políticas públicas: a construção de imagens e sentidos para o envelhecimento humano - França, Sônia Aparecida Moreira [UNESP]; Hashimoto, Francisco [UNESP]; Correa, Mariele Rodrigues [UNESP] (My University, 2010)
The present study aims to analyze the Brazilian public policies made for the elderly citizen population and to examine their resonance in the production of senses and images on the process of aging. For this, we draw cartographies that could find producing figures of sense about the aging, passing through some politics formulated for to this age group, since the decade of 1920 until the creation of the “Estatuto do Idoso”, in 2003. We checked that the appearance of public policies for the old age happened as an answer to the challenge of managing and controlling the aging process courses in front of the increase of the elderly citizen population. The “Estatuto do Idoso” is an important landmark of the management advance of the State upon the oldness and of the substitution of an philanthropic-assistance model for a preventive model which is based on the promotion of a healthy and productive longevity. With that, next to the figure of the sick and inactive elderly , it begins to appear figurations of a healthy and powerful aging, crossed by images of vitality and rejuvenation.

O presente estudo visa analisar as políticas públicas brasileiras dirigidas à população idosa e examinar suas ressonâncias na produção de sentidos e imagens sobre o processo de envelhecimento. Para tanto, procuramos traçar cartografias que pudessem mapear figuras produtoras de sentido acerca do envelhecimento, percorrendo algumas políticas formuladas para a essa faixa etária, desde a década de 1920 até a criação do Estatuto do Idoso, no ano de 2003. Verificamos que o aparecimento de políticas públicas para a velhice ocorreu como resposta ao desafio de se gerir e controlar os rumos do processo de envelhecimento diante do crescimento da população idosa. O Estatuto do Idoso é um marco importante do avanço da gestão do Estado sobre a velhice e da substituição de um modelo assistencialista-filantrópico para um modelo preventivo e calcado na promoção de uma longevidade saudável e produtiva. Com isso, ao lado da figura do idoso adoecido e inativo começam a surgir figurações de um envelhecimento saudável e potente, atravessadas por imagens de vitalidade e rejuvenescimento.
Public polices: the construction of images and senses for the human aging
Keywords: Old age; Public policies; Third age; Velhice; Políticas públicas; Terceira idade